The Influence of Financial Literacy on Investment Decisions During the Pandemic - Linzzy Pratami Putri; Irma Christiana; Umi Kalsum; Widya Widya; Meyyara Justianti (AIBPM Publisher, 2021)
This study aims to determine the effect of financial literacy on investment decisions during the pandemic. The object of this research is the students of the Faculty of Economics and Business, Universitas Muhammadiyah Sumatera Utara by using the Slovin formula in taking the sample. The test is carried out by simple linear regression where the classical assumptions have been tested previously. The results showed that there was a significant influence of financial literacy on investment decisions. The pandemic has made everyone, including students, start investing for future needs. Students are advised to continue to improve their financial literacy for the better. With increasing financial literacy, financial management will also be better and lead to investment.